2014
DOI: 10.1016/j.bmcl.2014.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nicotine and cotinine analogs as potential neuroprotective agents for Alzheimer’s disease

Abstract: The currently available therapies for Alzheimer’s disease (AD) and related forms of dementia are limited by modest efficacy, adverse side effects, and the fact that they do not prevent the relentless progression of the illness. The purpose of the studies described here was to investigate the neuroprotective effects of the nicotine metabolite cotinine as well as a small series of cotinine and nicotine analogs (including stereoisomers) and to compare their effects to the four clinically prescribed AD therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…The cerebral cortices from E17-18 Sprague-Dawley rat embryos were extracted and cultured as described elsewhere (Gao et al, 2014) under aseptic conditions. Timed pregnant rats were purchased from Harlan Sprague-Dawley (Indianapolis, IN) and housed and maintained on a 12-hour light/dark cycle in a temperature-controlled room (25°C) with free access to food and water for at least 3 days before initiating cultures.…”
Section: Embryonic Cortical Culturesmentioning
confidence: 99%
“…The cerebral cortices from E17-18 Sprague-Dawley rat embryos were extracted and cultured as described elsewhere (Gao et al, 2014) under aseptic conditions. Timed pregnant rats were purchased from Harlan Sprague-Dawley (Indianapolis, IN) and housed and maintained on a 12-hour light/dark cycle in a temperature-controlled room (25°C) with free access to food and water for at least 3 days before initiating cultures.…”
Section: Embryonic Cortical Culturesmentioning
confidence: 99%
“…Studies to date indicate that cotinine might have properties that would be potentially important for the treatment of AD, schizophrenia, and depression. For example, relevant to AD, cotinine has been shown to be cytoprotective and neuroprotective as demonstrated by its ability to improve the survival of differentiated PC12 cells deprived of nerve growth factor [40], as well as to protect primary cortical neurons from the neurotoxic effects of the amyloid beta (Aβ) peptide or glutamate [41,42]. Cotinine also improved working/short term memory in a delayed match to sample (DMTS) task in monkeys [43], prevented memory loss in an AD mouse model (Tg6799), stimulated the Akt/GSK3β pathway and reduced Aβ aggregation in their brains [44,45].…”
Section: Cotinine As a Prototypic Compound With “Multifunctional” mentioning
confidence: 99%
“…For example, in studies relevant to AD, cotinine has been shown to improve the survival of differentiated PC12 cells deprived of nerve growth factor (Buccafusco and Terry, 2003), as well as primary cortical neurons exposed to toxic concentrations of the amyloid-b peptide or glutamate Gao et al, 2014). Cotinine has also been shown to improve working/short-term memory performance in monkeys (Terry et al, 2005), prevent memory loss in transgenic 6799 Alzheimer's disease mice, and stimulate the Akt/GSK3b pathway and reduce amyloid-b aggregation in mouse brains Patel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%